2002
DOI: 10.1051/0004-6361:20021522
|View full text |Cite
|
Sign up to set email alerts
|

Tidal dwarf candidates in a sample of interacting galaxies

Abstract: Abstract. We present low-resolution spectroscopy of the ionized gas in a sample of optical knots located along the tidal features of 14 interacting galaxies previously selected as candidate Tidal Dwarf Galaxies (TDGs). From redshift measurements, we are able to confirm their physical association with the interacting system in almost all cases. For most knots, the oxygen abundance does not depend on the blue luminosity. The average, 12 + log(O/H) = 8.34 ± 0.20, is typical of TDGs and is comparable to that measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
146
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 57 publications
10
146
1
Order By: Relevance
“…In addition, luminosity-metallicity relations are very useful to discern between pre-existing dwarf galaxies and tidal dwarf galaxy (TDG) candidates (Duc & Mirabel 1998;Duc et al 2000) because these objects should have a metallicity similar to that observed in their parent spiral galaxies (Weilbacher et al 2003) and not a low-metallicity as it is found in dwarf objects.…”
Section: Metallicity-luminosity Relationsmentioning
confidence: 99%
“…In addition, luminosity-metallicity relations are very useful to discern between pre-existing dwarf galaxies and tidal dwarf galaxy (TDG) candidates (Duc & Mirabel 1998;Duc et al 2000) because these objects should have a metallicity similar to that observed in their parent spiral galaxies (Weilbacher et al 2003) and not a low-metallicity as it is found in dwarf objects.…”
Section: Metallicity-luminosity Relationsmentioning
confidence: 99%
“…In addition to atomic gas pulled from the parent galaxies, these collisional debris actually contain surprisingly large amounts of molecular gas formed in-situ (Braine et al 2000(Braine et al , 2001Lisenfeld et al 2002Lisenfeld et al , 2004Petitpas & Taylor 2005;Duc et al 2007). As the gas subsequently collapses, starforming regions are created with masses ranging from a few hundred solar masses, creating OB associations, the "emission line dots" (Gerhard et al 2002;Yoshida et al 2002;Sakai et al 2002;Weilbacher et al 2003;Ryan-Weber et al 2004;Mendes de Oliveira et al 2004;Cortese et al 2006;Werk et al 2008Werk et al , 2010 to objects as massive as dwarf galaxies named tidal dwarf galaxies (TDGs, Duc 1995;Duc & Mirabel 1998;Duc et al 2000Duc et al , 2007Hancock et al 2007Hancock et al , 2009). These objects, A&A 533, A19 (2011) even though formed from material once pertaining to their parent galaxies, have a radically different and simpler environment.…”
Section: Introductionmentioning
confidence: 99%
“…These so-called tidal dwarf galaxies (TDGs) share the high metallicity of the giant galaxies from which they formed, so are unusually metal-rich for their small size (e.g. Mirabel et al 1992; Duc et al 2000;Weilbacher et al 2003). They also have no or little non-baryonic DM, though may contain a significant fraction of baryonic DM (Bournaud et al 2007).…”
Section: Introductionmentioning
confidence: 99%